2017
DOI: 10.1016/j.radonc.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Heart dosimetric analysis of three types of cardiac toxicity in patients treated on dose-escalation trials for Stage III non-small-cell lung cancer

Abstract: Background and Purpose To assess associations between radiation dose/volume parameters for cardiac subvolumes and different types of cardiac events in patients treated on radiation dose-escalation trials. Material and Methods Patients with Stage III non-small-cell lung cancer received dose-escalated radiation (median 74 Gy) using 3D-conformal radiotherapy on six prospective trials from 1996–2009. Volumes analyzed included whole heart, left ventricle (LV), right atrium (RA), and left atrium (LA). Cardiac even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 44 publications
1
78
1
1
Order By: Relevance
“…Wang et al assessed the types of cardiac events in patients treated on dose-escalation trials for stage III non-small-cell lung cancer. Pericardial (pericardial effusions or pericarditis), ischemic (myocardial infarction or unstable angina), and arrhythmic (significant arrhythmia) events were correlated with whole-heart doses and other parameters [57]. Ventricular dysfunction from cardiac RT can also lead to systolic or diastolic function.…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al assessed the types of cardiac events in patients treated on dose-escalation trials for stage III non-small-cell lung cancer. Pericardial (pericardial effusions or pericarditis), ischemic (myocardial infarction or unstable angina), and arrhythmic (significant arrhythmia) events were correlated with whole-heart doses and other parameters [57]. Ventricular dysfunction from cardiac RT can also lead to systolic or diastolic function.…”
Section: Discussionmentioning
confidence: 98%
“…30 In stage III non-small-cell lung cancer, different cardiac events were associated with distinct heart volume doses; for example, ischemic events were correlated with left ventricle and whole heart dose. 27 The mean V 5 , V 10 , V 20 , V 30 We recognize that the study presents several limitations. First, this is a longitudinal study with a small sample size.…”
Section: Ta B L E 2 Relationship Between Heart Dose Parameters and Stmentioning
confidence: 95%
“…Accumulated results from clinical studies have shown that high cardiac radiation dose is directly associated with RIHDs. 24,[27][28][29] Oncologists must also consider the rate of cancer control and the dose of cardiac radiation when formulating a RT regimen. In childhood cancer survivors, a large sample case control study revealed that heart failure often occurred in patients that received ≥30 Gy to the median volume of the heart.…”
Section: Ta B L E 2 Relationship Between Heart Dose Parameters and Stmentioning
confidence: 99%
“…Cardiac events occurred within the first 5 years and continued several decades post-radiotherapy (7). Other studies have also examined the association between mean heart dose and cardiac events/disease, finding an ∼4-16% increased risk per Gy of mean heart dose (7)(8)(9). Studies have also suggested RIHD can occur in non-small cell lung cancer patients within 2 years post-radiation exposure (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Other studies have also examined the association between mean heart dose and cardiac events/disease, finding an ∼4-16% increased risk per Gy of mean heart dose (7)(8)(9). Studies have also suggested RIHD can occur in non-small cell lung cancer patients within 2 years post-radiation exposure (8)(9)(10)(11). In a number of lung cancer studies, mortality rates were cardiac dose-dependent, either based on mean heart dose (12) or with the percent of heart receiving 5 Gy (13), 30 Gy (13), or 50 Gy (10).…”
mentioning
confidence: 99%